Paediatric biobanking for health: The ethical, legal, and societal landscape - Casati, Sara; Ellul, Bridget; Mayrhofer, Michaela Th.; Lavitrano, Marialuisa; Caboux, Elodie; Kozlakidis, Zisis (Frontiers in Public Health, 2022)
Biobanks play a central role in paediatric translational research, which deals primarily with genetic data from sample-based research. However, participation of children in biobanking has received only limited attention in the literature, even though research in general and in clinical trials in particular have a long history in involving minors. So, we resolved to explore specific challenging ethical, legal and societal issues (ELSI) in the current paediatric biobanking landscape to propose a way forward for biobanking with children as partners in research. Methodologically, we first established the accessibility and utilisation of paediatric biobanks, mainly in Europe. This was supported by a literature review related to children's participation, taking into account not only academic papers but also relevant guidelines and best-practices. Our findings are discussed under five themes: general vulnerability; ethical issues - balancing risks and benefits, right to an open future, return of results including secondary findings; legal issues - capacity and legal majority; societal issues - public awareness and empowerment; and responsible research with children. Ultimately, we observed an on-going shift from the parents’/guardians' consent being a sine-qua-non condition to the positive minor's agreement: confirming that the minor is the participant, not the parent(s)/guardian(s). This ethical rethinking is paving the way towards age-appropriate, dynamic and participatory models of involving minors in decision-making. However, we identified a requirement for dynamic tools to assess maturity, a lack of co-produced engagement tools and paucity of shared best practices. We highlight the need to provide empowerment and capability settings to support researchers and biobankers, and back this with practical examples. In conclusion, equipping children and adults with appropriate tools, and ensuring children's participation is at the forefront of responsible paediatric biobanking, is an ethical obligation, and a cornerstone for research integrity.